Ketogenic metabolic therapy for schizoaffective disorder: a retrospective case series of psychotic symptom remission and mood recovery - Laurent, Nicole; Bellamy, Erin L.; Tague, Katherine A.; Hristova, Donika; Houston, Ally (Frontiers in Nutrition, 2025)
BackgroundSchizoaffective disorder is a severe psychiatric condition characterized by mood disturbances and psychotic symptoms. Standard treatments, primarily pharmacological, often fail to control symptoms fully and can lead to significant metabolic side effects. Emerging evidence suggests that ketogenic metabolic therapy (KMT), also known as the ketogenic diet, may offer a powerful alternative to conventional treatments for mood components and resolve psychiatric symptoms in patients with schizoaffective disorder.MethodsThis case series investigates the effects of KMT on two individuals diagnosed with schizoaffective disorder who pursued this therapy due to the ineffectiveness of conventional treatments. Both case presentations followed a modified ketogenic diet with medical oversight. Symptom changes in mood were assessed using validated tools, including the Generalized Anxiety Disorder-7 (GAD-7), Depression Anxiety Stress Scales (DASS-42), PTSD Checklist for DSM-5 (PCL-5), and Patient Health Questionnaire-9 (PHQ-9).ResultsBoth case presentations experienced the complete cessation of psychotic symptoms and improvements in mood. Case 1, a 17-year-old female, achieved full remission of severe suicidal ideation, hallucinations, and anxiety within 6 weeks, with sustained improvements at a 24-week follow-up. Case 2, a 32-year-old female, achieved full remission of chronic psychotic and mood symptoms by 6 months. Patients either achieved full psychiatric deprescription or were in the process of deprescription at time of follow-up.ConclusionThis case series demonstrates that ketogenic metabolic therapy can resolve chronic psychotic and mood symptoms in patients with schizoaffective disorder, leading to full remission and significant functional recovery and reported improvements in quality of life that extend beyond symptom control with standard of care interventions.